A Review on the Prevalence of Poxvirus Disease in Free-Living and Captive Wild Birds - Richard A. J. Williams; Daniel A. Truchado; Laura Benitez (Microbiology Research, 2021)
Avian pox is a widespread infection in birds caused by genus Avipoxvirus pathogens. It is a noteworthy, potentially lethal disease to wild and domestic hosts. It can produce two different conditions: cutaneous pox, and diphtheritic pox. Here, we carry out an exhaustive review of all cases of avian pox reported from wild birds to analyze the effect and distribution in different avian species. Avian poxvirus strains have been detected in at least 374 wild bird species, a 60% increase on a 1999 review on avian pox hosts. We also analyze epizootic cases and if this disease contributes to wild bird population declines. We frequently observe very high prevalence in wild birds in remote island groups, e.g., Hawaii, Galapagos, etc., representing a major risk for the conservation of their unique endemic avifauna. However, the difference in prevalence between islands and continents is not significant given the few available studies. Morbidity and mortality can also be very high in captive birds, due to high population densities. However, despite the importance of the disease, the current detection rate of new Avipoxvirus strains suggests that diversity is incomplete for this group, and more research is needed to clarify its real extent, particularly in wild birds.